METHODICAL SYSTEM OF FOREIGN LANGUAGE TRAINING OF FUTURE SOCIAL SPHERE SPECIALISTS - Павелкив, Екатерина (Modern engineering and innovative technologies, 2019)
The article presents the analysis of the condition and problems of foreign language training in Ukraine. The scientific and theoretical survey of native and foreign studies on the problem is carried out. The article shows the results of methodical system